2019
DOI: 10.1097/brs.0000000000002897
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Imbalance in Adult Spinal Deformity Following Posterior Spinal Fusion With Instrument

Abstract: Study Design. A retrospective radiographic study. Objective. To explore the radiological parameters which correlated to postoperative immediately coronal imbalance in adult spinal deformity (ASD) and to determine whether preoperative coronal imbalance affects postoperative coronal imbalance following posterior multi-level fusion with instruments and osteotomy operation. Summary of Background Data. There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 18 publications
6
31
0
Order By: Relevance
“…In the study by Ploumis et al, 3 9 of 54 patients were in balance preoperatively and had developed new CM (defined as > 4 cm in their study) at last follow-up. Similarly, Zhang et al 6 reported that 16 of 51 patients in the type A category developed CM postoperatively (> 3 cm). Certainly, this finding does not suggest that cMIS is superior to open techniques in this group of patients, because there are likely to be considerable differences in our sample of patients that limit any direct comparisons between studies.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the study by Ploumis et al, 3 9 of 54 patients were in balance preoperatively and had developed new CM (defined as > 4 cm in their study) at last follow-up. Similarly, Zhang et al 6 reported that 16 of 51 patients in the type A category developed CM postoperatively (> 3 cm). Certainly, this finding does not suggest that cMIS is superior to open techniques in this group of patients, because there are likely to be considerable differences in our sample of patients that limit any direct comparisons between studies.…”
Section: Discussionmentioning
confidence: 83%
“…to make large sagittal corrections and restore lordosis in patients with adult spinal deformity, it has been demonstrated that the correction of coronal malalignment (CM) is often poor and leads to worse outcomes. [3][4][5][6] Interest in the correction of coronal alignment has recently been renewed. In 2016, Bao et al 5 described a classification of coronal imbalance and divided patients into groups on the basis of whether their C7 plumb line was neutral (type A), shifted toward the concavity (type B), or shifted toward the convexity (type C) of their scoliosis.…”
mentioning
confidence: 99%
“…The increasing imbalance on the coronal plane in patients with degenerative lumbar scoliosis (DLS) has become one of main underlying factor that leads them to abnormal appearance, functional decline, and back pain [17] . The distance between C7 plumb line (C7PL) and central sacral vertical line (CSVL), named coronal balance difference [5] , coronal balance distance [12] , global coronal malalignment [14] , and C7 migration [11] , has been used to re ect coronal alignment. In this current study, we de ned the global coronal parameter as coronal balance distance (CBD).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, considering correction of main curve during long-fusion surgery in ASD patients, Zhang et al [12] suggested that there is signi cant correlation among pre-operative CBD, recti ed Cobb angle of main curves, and post-operative CBD. Unfortunately, they did not explore the relationship between major curve and CBD further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation